Environmental planning and management (EPM) source book - United Nations Centre for Human Settlements (United Nations Centre for Human Settlements : United Nations Environment Programme, 1997)
Why Improve the Urban Environment; How Cities Improve the Urban Environment; How Programmes Support Cities; Sharing Lessons of Experience and Advancing Collective Knowâˆ’How.